Kepastian Hukum Pelaksanaan Lelang Terhadap Pemenang Lelang pada Saat Penyerahan Obyek - Septianingrum, Mia; Santoso, Budi (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study discusses what if it turns out that the auction object when its obligations have been paid off by the buyer is not appropriate? If there is a legal vacuum, then what can be done to protect the buyer's rights? This study was conducted in order to answer questions like this, and then to be able to provide legal certainty and also legal protection for the parties involved in the auction. This research method is normative juridical. The approach used is the statutory approach (Statute Approach) and the conceptual approach (Conceptual Approach). Several studies show that auction winners often face delays in receiving auction objects due to administrative procedures or in moving auctions, the goods submitted are not appropriate. This arises because the laws and regulations regarding auctions are very minimal. The latest regulation is seen, namely the Minister of Finance, such as the Regulation of the Minister of Finance Number 27 of 2016 concerning Auction Implementation Guidelines. This results in a legal vacuum in several matters regarding auctions. One of them is if the auction object that is submitted during the delivery period is then not appropriate. Because this is not regulated in existing laws and regulations, it results in legal uncertainty for auction buyers.